Patterns of collective organization associated with positive and negative momentum experiences in football: An expert coach description-based analysis - Gautier, H.; Cavailles, O.; Gernigon, C. (Journal of Human Sport & Exercise, 2024)
Purpose: Momentum experiences in sport competition are known to be associated with performance-related behavioural changes. In addition to effort exertion, interpersonal synchronization in small team sports has been identified as a behavioural correlate of momentum experiences. However, there is a lack of research on collective organization related to momentum in larger team sports. The present study aimed to identify and compare patterns of collective organization in football according to positive and negative momentum experiences in the form of gradual and significant score variations.